On the feasibility of magma fracture within volcanic conduits: Constraints from earthquake data and empirical modelling of magma viscosity - De Angelis, S.; Henton, S. M. (Geophysical research letters, 2011)
In the last decade several studies have indicated that magma within volcanic conduits can undergo repeated failure and healing, thus, providing a realistic source mechanism for the peculiar sequences of low‐frequency earthquakes that often announce eruptions. Although geological observations, laboratory experiments, and numerical modelling support such a hypothesis, the links between geophysical observations and the proposed models remain qualitative. This study focuses on providing constraints to the relationship between the occurrence of repeating earthquakes and magma fracture at andesite volcanoes. Empirical modelling of viscosity is incorporated into the fundamental physics of magma fracture in order to assess whether and where the conditions for brittle failure are met within volcanic conduits. A case study from the 1995‐ongoing eruption of Soufrière Hills Volcano, Montserrat, is presented. The locations of earthquakes from a pre‐eruptive low‐frequency seismic swarm illuminate a relatively compact source volume at depths of 100–300 meters below sea level. Viscosity modelling confirms that the Soufrière Hills magma could rupture at those depths. Key Points Shear fracture of magma is feasible at shallow depth in volcanic conduits High magma crystallinity and/or elevated strain rates are necessary LF earthquake locations are compatible with magma fracture processes